Primer registro del género Jenynsia Günther, 1866 (Teleostei: Cyprinodontiformes) en el Pleistoceno Medio tardío de la provincia de Buenos Aires (Argentina) - Bogan, Sergio (2009)
In this article, we described a left premaxilla assigned to Jenynsia, recovered in lacustrine facies corresponding to the Bonaerian Stage-Age (Late Middle Pleistocene) from Centinela del Mar, Buenos Aires Province, Argentina. This material constitutes the first fossil record of the genus and one among the few antecedents of the Anablepidae family. The finding communicated here offers new evidence towards the understanding of the Quaternary South American ichthyofaunas.